2009
DOI: 10.1007/s10529-009-0124-0
|View full text |Cite
|
Sign up to set email alerts
|

Fed-batch operation of an industrial cell culture process in shaken microwells

Abstract: Recently we have demonstrated batch suspension culture of mammalian cells in microwell plates. Here we describe a method for fed-batch culture of an industrially relevant GS-CHO (Glutamine Synthetase-Chinese Hamster Ovary) cell line in shaken 24-standard round well (24-SRW) plates. Use of a commercially available 'sandwich lid' and appropriate dilution of the bolus feeds counteracted liquid evaporation from the wells resulting in similar cell growth and antibody formation kinetics in both 24-SRW plates (800 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 17 publications
(16 reference statements)
1
26
0
Order By: Relevance
“…Caution must be exerted however, as the expression of a putative cell surface galactosyltransferase (Penno et al, ) and the presence of glycosidases (Porwoll et al, ) in the culture medium released by dead cells may influence terminal galactosylation of cell surface proteins, affecting the extent of correlation between cell surface lectin binding and MAb β1,4‐galactose levels. When taken in to account, by exploiting the advantages of cell surface glycan screening in a live‐cell lectin microarray format (Li et al, ; Tao et al, ; Tateno et al, ), there is potential to couple the technology to microscale cell culture systems and high throughput product titre measurement (Amanullah et al, ; Legmann et al, ; Silk et al, ) to rapidly identify culture conditions that result in cell lines with favourable productivity and desirable glycan processing. Rapid screening of cell lines in this way permits a level of feedback control, identifying promising production cell line candidates with ideal glycan processing early in development which can then undergo further manipulation during process optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…Caution must be exerted however, as the expression of a putative cell surface galactosyltransferase (Penno et al, ) and the presence of glycosidases (Porwoll et al, ) in the culture medium released by dead cells may influence terminal galactosylation of cell surface proteins, affecting the extent of correlation between cell surface lectin binding and MAb β1,4‐galactose levels. When taken in to account, by exploiting the advantages of cell surface glycan screening in a live‐cell lectin microarray format (Li et al, ; Tao et al, ; Tateno et al, ), there is potential to couple the technology to microscale cell culture systems and high throughput product titre measurement (Amanullah et al, ; Legmann et al, ; Silk et al, ) to rapidly identify culture conditions that result in cell lines with favourable productivity and desirable glycan processing. Rapid screening of cell lines in this way permits a level of feedback control, identifying promising production cell line candidates with ideal glycan processing early in development which can then undergo further manipulation during process optimisation.…”
Section: Discussionmentioning
confidence: 99%
“…Fed‐batch cultures were performed by feeding cells every 2 days with an in‐house feed solution. For the 96DW fed‐batch cultures, the inoculation and feeding processes were performed using the Hamilton robot (Hamilton, Reno, NV, USA), with nutrient feed being diluted with water to counteract reductions in volume due to evaporation . Only one sample was removed for titer or cell number determination during the fed‐batch in the 96DW plates and one sample was removed at the end.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, growth phenotypes, likely induced by ventilation or temperature effects within the incubation chamber (Pacheco et al, ) or uneven CO 2 mass transfer into the wells (Han et al, ), were observed. With regard to extended cultivation times, evaporation control needs to be evaluated carefully, as high liquid loss may distort cultures’ performance (Betts et al, ; Silk et al, ). Many of the systems presented use top side illumination of the MTP potentially impeding the use of appropriate sterile barriers ensuring monoseptic conditions and restricting the accessibility with respect to integration into laboratory robotic platforms.…”
Section: Introductionmentioning
confidence: 99%